Konvergensi Media dan Perubahan dalam Manajemen SDM Media - Bawapratama, Choky Rais (Jurnal Komunikasi, 2011)
Technological development always gives change to the mass media, including the online media presence. The presence of online media allows the occurrence of convergent media that have a variety of formats in a single display. Convergence becomes a threat on the one side and a chance in the other. It requires ability to master the technology and also individuals who are adaptable and made for different multimedia working patterns. This research is based on the different characteristics both in the writing, working patterns, and culture of the organization along with increasing media formats. This is the most influential to the media’ editorial staff. The study formulates problems in two ways. First is how media convergence policy brings change to the management of Human Resources (HR) section in Solopos Daily. The second is how the Human Resources Editorial Staff of Solopos Daily adapts to the changes in HR management that occur as a result of media convergence.